Clusters, imperfect competition markets, and self-organization: the economy as a complex system - Acuña O, Marvin (2013)
Complex systems ruled by principles such as self-organization, interaction,interdependence, back-feeding, initial conditions sensitivity and continuous emergence and adaptation, is a new theoretical approach, still not very used to analyze space issues of production organization and/or market structure leading to clusters or firm’s networking. theoretical as well as methodological goodness of such complex systems, explaining how clusters emerge and their functioning patterns are here explored. According to theory, it turns out that is imperfect competition which gives rise to this kind of firm’s arrangements, and that it is increasing returns which make more attractive for enterprises to establish themselves nearby certain economic activity within a territory, ie, these special attributes are main gathering forces for clustering firms. determining whether clusters are complex systems of self-organizing space production pattern or not is addressed in this paper, ie, that imperfect competition lies under the process of clustering, which in turn is a complex, open and non-linear production organizing system evolving endogenously thorough changing and adapting processes, which at last, is the structuring axis of the cluster.